Correction to: Influence of physical training on erythrocyte concentrations of iron, phosphorus and magnesium - Marcos Maynar Mariño; Francisco Javier Grijota; Ignacio Bartolomé; Jesús Siquier-Coll; Victor Toro Román; Diego Muñoz (Taylor & Francis Group, 2020)
An amendment to this paper has been published and can be accessed via the original article.